Societal influence and psychological distress among Indonesian adults in Java on the early Omicron wave of COVID-19 - Annette d'Arqom; Muh Akram; Nafesa Shafira Azzahranisa; Mhd Zamal Nasution; Endang Retno Surjaningrum; Junaidah Yusof (Future Science OA, 2023)
Aim: Changes during the COVID-19 pandemic might create pressure on different people, thus this study aimed to measure respondents' psychological distress during the early phase of the Omicron wave in Java Island. Methods: A web-based survey on societal influence and COVID-19-related psychological distress was distributed through social media in November–December 2021, and received 396 responses. Results: This study showed that almost 50% of respondents faced psychological distress during the early phase of the Omicron variant, especially concerning hypervigilance and avoidance. Several sociodemographic factors might contribute to the incidence of psychological distress including comorbidity, age and education. Conclusion: Taken together, the incidence of COVID-19-related psychological distress was still found in the early phase of the Omicron variant, especially among young adults.